Precision isolation and cultivation of single cells by vortex and flat-top laser ejection - Chen, Fuyuan; Liu, Kunxiang; Shang, Lindong; Wang, Yuntong; Tang, Xusheng; Liang, Peng; Li, Bei (Frontiers in Microbiology, 2024)
Single-cell isolation stands as a critical step in single-cell studies, and single-cell ejection technology based on Laser Induced Forward Transfer technology (LIFT) is considered one of the most promising methods in this regard for its ability of visible isolating single cell from complex samples. In this study, we improve the LIFT technology and introduce Optical Vortex Laser-Induced Forward Transfer (OV-LIFT) and Flat-Top Laser-Induced Forward Transfer (FT-LIFT) by utilizing spatial light modulator (SLM), aiming to enhance the precision of single-cell sorting and the cell's viability after ejection. Experimental results demonstrate that applying vortex and flat-top beams during the sorting and collection process enables precise retrieval of single cells within diameter ranges of 50μm and 100μm respectively. The recovery rates of Saccharomyces cerevisiae and E. coli DH5α single cell ejected by vortex beam are 89% and 78%, by flat-top beam are 85% and 57%. When employing Gaussian beam sorting, the receiving range extends to 400μm, with cultivation success rates of Saccharomyces cerevisiae and E. coli DH5α single cell are 48% and 19% respectively. This marks the first application of different mode beams in the ejection and cultivation of single cells, providing a novel and effective approach for the precise isolation and improving the viability of single cells.